Accounting for Variable Task Discrimination in Divergent Thinking Fluency Measurement: An Example of the Benefits of a 2‐Parameter Poisson Counts Model and its Bifactor Extension Over the Rasch Poisson Counts Model. (6th January 2021) - Myszkowski, Nils; Storme, Martin
Abstract: Fluency tasks are among the most common item formats for the assessment of certain cognitive abilities, such as verbal fluency or divergent thinking. A typical approach to the psychometric modeling of such tasks (e.g., Intelligence, 2016, 57, 25) is the Rasch Poisson Counts Model (RPCM; Probabilistic models for some intelligence and attainment tests . Copenhagen: Danish Institute for Educational Research, 1960), in which, similarly to the assumption of (essential) τ ‐equivalence in Classical Test Theory, tasks have equal discriminations—meaning that, beyond varying in difficulty, they do not vary in how strongly they are related to the latent variable. In this research, we question this assumption in the case of divergent thinking tasks, and propose instead to use a more flexible 2‐Parameter Poisson Counts Model (2PPCM), which allows to characterize tasks by both difficulty and discrimination. We further propose a Bifactor 2PPCM (B2PPCM) to account for local dependencies (i.e., specific/nuisance factors) emerging from tasks sharing similarities (e.g., similar prompts and domains). We reanalyze a divergent thinking dataset ( Psychology of Aesthetics, Creativity, and the Arts, 2008, 2, 68) and find the B2PPCM to significantly outperform the 2PPCM, both outperforming the RPCM. Further extensions and applications of these models are discussed.